Marine Bioactive Compounds Derived from Macroalgae as New Potential Players in Drug Delivery Systems: A Review - Bogdan-Stefan Ne; Ticuta Negreanu-Pirjol; Dan Razvan Popoviciu; Ruxandra-Elena Anton; Ana-Maria Prelipcean (MDPI AG, 2022)
The marine algal ecosystem is characterized by a rich ecological biodiversity and can be considered as an unexploited resource for the discovery and isolation of novel bioactive compounds. In recent years, marine macroalgae have begun to be explored for their valuable composition in bioactive compounds and opportunity to obtain different nutraceuticals. In comparison with their terrestrial counterparts, Black Sea macroalgae are potentially good sources of bioactive compounds with specific and unique biological activities, insufficiently used. Macroalgae present in different marine environments contain several biologically active metabolites, including polysaccharides, oligosaccharides, polyunsaturated fatty acids, sterols, proteins polyphenols, carotenoids, vitamins, and minerals. As a result, they have received huge interest given their promising potentialities in supporting antitumoral, antimicrobial, anti-inflammatory, immunomodulatory, antiangiogenic, antidiabetic, and neuroprotective properties. An additional advantage of ulvans, fucoidans and carrageenans is the biocompatibility and limited or no toxicity. This therapeutic potential is a great natural treasure to be exploited for the development of novel drug delivery systems in both preventive and therapeutic approaches. This overview aims to provide an insight into current knowledge focused on specific bioactive compounds, which represent each class of macroalgae e.g., ulvans, fucoidans and carrageenans, respectively, as valuable potential players in the development of innovative drug delivery systems.